Correction: Elucidating the formation and active state of Cu co-catalysts for photocatalytic hydrogen evolution. Issue 41 (13th October 2021) - Schubert, Jasmin S.; Kalantari, Leila; Lechner, Andreas; Giesriegl, Ariane; Nandan, Sreejith P.; Ayala, Pablo; Kashiwaya, Shun; Sauer, Markus; Foelske, Annette; Rosen, Johanna; Blaha, Peter; Cherevan, Alexey; et al.
Abstract : Correction for 'Elucidating the formation and active state of Cu co-catalysts for photocatalytic hydrogen evolution' by Jasmin S. Schubert et al., J. Mater. Chem. A, 2021, DOI: ; 10.1039/d1ta05561e .